The diversity of democracy : corporatism, social order and political conflict - Crouch, Colin; Streeck, Wolfgang (UK : Edward Elgar, 2006)
Focusing on the classical literature on neo-corporatism, this book illustrates the enormous influence of the 'neo-corporatist debate' on modern political science, political sociology, and political economy. It is aimed at academics, students and researchers with an interest in political science, democratic theory and European integration.
Includes index.
Keywords: Corporate state; Social conflict; Democracy